To the Conception of Existoencephalic System of Cooled Brain. Part 5. Fractal Homeometry of Structural and Functional State of Immune and Cardiovascular System Under Cold Stress - Babiychuk, V. G.; Grischenko, V. I.; Marchenko, V. S.; Babiychuk, G. A.; Marchenko, L. N. (Problems of Cryobiology and Cryomedicine, 2006)
Using the methods of fractal morphometry, histological, histochemical electron-microscopic analysis there was investigated structural and functional state of immune and cardiovascular system under stress effects of different genesis. It was demonstrated that myocardium structure during cold stress had considerable fractal properties in contrast to thymus. Dynamics of the interchange of persistence and antipersistence in heart and brain is of an anti-phase character.